Evaluation of the predictive value of fetal Doppler ultrasound for neonatal outcome from the 36(th) week of pregnancy - Eslamian, Zahra Laleh (J Res Med Sci, 2018)
BACKGROUND: Early prediction of adverse neonatal outcome would be possible by Doppler impedance indices of middle cerebral artery (MCA), umbilical artery (UmA), and descending aortal artery (AO) that result in decrease neonatal morbidity and mortality rate. The aim of the present study was a determination of optimal value for the ratio of MCA to descending aorta blood flow (MCA/AO) impedance indices and its comparison with the ratio of MCA to UmA (MCA/UmA) impedance indices and their relationship with neonatal outcome. MATERIALS AND METHODS: This was a prospective cohort study on 212 pregnant women with gestational age 36 weeks or more, in three hospitals in Tehran, from April 2012 to April 2013. We investigated AO, MCA, and UmA impedance indices Doppler ultrasound every 2 weeks till delivery. The mother was monitored for adverse pregnancy outcome (hypertension [HTN], fetal growth retardation, and other maternal complications) then infant birth weight, cord blood of pH, and Neonatal Intensive Care Unit (NICU) admission during the first 24 h after delivery were assessed. Finally, we investigated relationships between Doppler indices and neonatal outcomes include neonatal body weight (NBW), cord blood of pH, and NICU admission. RESULTS: MCA/AO resistance index (RI) and MCA/AO pulsatile index (PI) showed an area under the receiver operating characteristics curve (area under the curve) of 0.905 (95% confidence interval (CI): 0.850, 0.959) and 0.818 (95% CI: 0.679, 0.956), respectively. The cutoff values for pH (≥7.2 vs. <7.2) based on MCA/AO RI and MCA/AO PI indices were 0.951 (sensitivity, 80% and specificity, 86%) and 0.853 (sensitivity, 91% and specificity, 83%), respectively. The cutoff value for NBW (≥2500 vs. <2500 g) based on MCA/UmA PI index was 1.467 (sensitivity, 73% and specificity, 63%). The cutoff value of NICU admission of child based on MCA/AO PI index was 1.114 (sensitivity, 73% and specificity, 54%). CONCLUSION: In the end of third-trimester pregnancies with the assessment of MCA and AO artery Doppler ultrasonography, it is possible to prevent many cases of neonatal acidosis caused by prenatal asphyxia as well as inappropriate interventions which are applied on mother. If MCA/AO PI was <0.85, the fetus needs to be evaluated further because it is at risk for acidosis.